Financial elements in job satisfaction of special education teachers in Malaysia - Ali, Syahrul Anuar; Mustapha, Khadijah; Johari, Jalila; Elias, Sofia; Nordin, Mohd Norazmi (Science Research Society, 2021)
The financial element is among the top -ranked elements in the job satisfaction construct related to head teacher leadership. This statement suggests that, teachers ’finances affect job satisfaction, based on its relationship with head teacher leadership. Although this element is not a key element that impacts the construct of teacher job satisfaction, it remains significantly related to head teacher leadership. There are also studies that found that the relationship between head teacher leadership and teacher job satisfaction is at a weak level, from the aspect of financial element. Maslow’s theory clearly discusses related financial elements in explaining teacher job satisfaction. The theory basically states that finance is a necessity for a person to achieve satisfaction in work. Therefore, headmasters who manage PPKI need to emphasize the financial element to ensure smooth management and provide space for teacher job satisfaction. This qualitative study involved 11 coordinators of special education integration programs (PPKI) in the state of Johor, Malaysia. All respondents were interviewed to get their perceptions related to the financial element in meetingjob satisfaction.